2012
DOI: 10.1530/erc-11-0306
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-specific ablation of the Carney complex gene, PRKAR1A, results in hyperthyroidism and follicular thyroid cancer

Abstract: Thyroid cancer is the most common endocrine malignancy in the population, and the incidence of this cancer is increasing at a rapid rate. Although genetic analysis of papillary thyroid cancer (PTC) has identified mutations in a large percentage of patients, the genetic basis of follicular thyroid cancer (FTC) is less certain. Thyroid cancer, including both PTC and FTC has been observed in patients with the inherited tumor predisposition Carney Complex (CNC), caused by mutations in PRKAR1A. In order to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…A number of genetic lesions have been identified in human FTC, including mutations in RAS, PTEN, and the PPARG-PAX8 fusion gene, but the connection between these mutations and carcinogenesis is less clear, especially because mouse models carrying these mutations singly either do not generate FTC (Ras and Pparg-Pax8) or generate it only unreliably (Pten deletion). In contrast, we recently demonstrated that thyroid-specific KO of Prkar1a leads to FTC in more than 40% of mice by 1 year of age (8). However, these tumors did not exhibit hematogenous metastasis, a key feature of human FTC.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A number of genetic lesions have been identified in human FTC, including mutations in RAS, PTEN, and the PPARG-PAX8 fusion gene, but the connection between these mutations and carcinogenesis is less clear, especially because mouse models carrying these mutations singly either do not generate FTC (Ras and Pparg-Pax8) or generate it only unreliably (Pten deletion). In contrast, we recently demonstrated that thyroid-specific KO of Prkar1a leads to FTC in more than 40% of mice by 1 year of age (8). However, these tumors did not exhibit hematogenous metastasis, a key feature of human FTC.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to data from R1a- (8) and DRP-TpoKO mice, we also generated microarray data from our own colony of Pten-TpoKO mice, which exhibit benign follicular thyroid hyperplasia (Supplemental Table 3). These three mouse data sets were used to perform principal component (PC) analysis to compress and then identify trends in the data.…”
Section: Microarray Analyses Confirm Activation Of Network Related Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the thyroid-specific knockout of the PRKAR1A gene in mice also resulted in hyperthyroidism, and papillary and follicular thyroid cancer (26).…”
Section: Del Gobbo a Et Almentioning
confidence: 96%
“…STAT3 is typically activated through phosphorylation at tyrosine 705 by intrinsic tyrosine kinase activity of activated growth factor receptors or cytokine receptor-associated Janus kinase, but GasPCR/adenylyl cyclase/cAMP/PKA signaling can also activate STAT3. [124][125][126][127] For example, G-protein a-subunit-activating mutations in sporadic benign and malignant liver tumors are characterized by an inflammatory phenotype associated with STAT3 activation. 126 The…”
Section: Interstitial Inflammation and Fibrosismentioning
confidence: 99%